Surgical Treatment vs Nonsurgical Treatment for Brain Arteriovenous Malformations in Patients with Hereditary Hemorrhagic Telangiectasia: A Retrospective Multicenter Consortium Study - Meybodi, Ali Tayebi (Neurosurgery, 2018)
BACKGROUND: Cerebral arteriovenous malformations (AVMs) are common in patients with hereditary hemorrhagic telangiectasia (HHT). However, due to the rarity of HHT and little published evidence of outcomes from management of brain AVMs in this disease, current international HHT guidelines recommend an individualized approach. Specifically, the outcomes for surgical vs nonsurgical management of these lesions have not been reported to date. OBJECTIVE: To report long-term outcomes of surgical resection of brain AVMs in HHT patients compared to outcomes in nonsurgically treated patients. METHODS: From the database of the Brain Vascular Malformation Consortium HHT project, 19 patients with 20 resected AVMs (group 1) and 22 patients with 33 AVMs who received nonsurgical treatment (group 2) were studied. The groups were retrospectively reviewed for changes in functional status (modified Rankin Scale score) during the follow-up period. RESULTS: During the follow-up period, 9% of patients in group 1 suffered from worsening of functional status, whereas this figure was 16% for group 2 (P > .05). Functional outcomes were not statistically different between the 2 groups at the latest follow-up (P > .05). CONCLUSION: HHT patients treated surgically for brain AVMs appear to have long-term functional outcomes comparable to nonsurgical (including observational) therapy with fewer unfavorable outcomes. It is therefore reasonable to consider surgical resection as a management option in the multidisciplinary team's individualized treatment strategy for HHT patients with brain AVMs.